Molecular Biomarkers in Drug-Induced Liver Injury: Challenges and Future Perspectives - Fu, Siyu; Wu, Dongbo; Jiang, Wei; Li, Juan; Long, Jiang; Jia, Chengyao; Zhou, Taoyou (Frontiers in Pharmacology, 2020)
Drug-induced liver injury (DILI) is one among the common adverse drug reactions and the leading causes of drug development attritions, black box warnings, and post-marketing withdrawals. Despite having relatively low clinical incidence, its potentially severe adverse drug reaction should be considered in the individual patient due to the high risk of acute liver failure. Although some traditional liver parameters have been applied to the diagnosis of DILI, a major limitation in its diagnosis relies on currently lacking specific and sensitive biomarkers, and thus prediction of the subsequent clinical course is still difficult to make. These drawbacks prompt the investigation and discovery of more effective biomarkers, which could lead to early detection of DILI, and improve its diagnosis and prognosis. New promising biomarkers include glutamate dehydrogenase, keratin 18, sorbitol dehydrogenase, glutathione S-transferase, bile acids, cytochrome P450, osteopontin, high mobility group box-1 protein, fatty acid binding protein 1, cadherin 5, miR-122, genetic testing and others. Besides those potential biomarkers, several clinical scoring systems gradually emerged in the diagnosis of DILI, such as RUCAM, CDS, and DDW-J. However, their predictive value is still limited with certain deficiencies. Perhaps the greatest benefit could be obtained from combining the scoring systems and those biomarkers. Hence, we summarized the recent research progress of molecular biomarkers for DILI in order to provide better approaches for its diagnosis and clinical management.